PENGARUH PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV GUGUS V KABUPATEN SITUBONDO - Ahmad Zainullah; Mufarrahatus Syarifah (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2015)
Teachers always use a context on explaining the concepts, when they use RME. RME could become an alternative on mathematics instruction, where the instruction usually is held by expository method. This study is aim to know the effect of RME to the students’ report. By comparing students’ report, between they were teach using RME and expository, the result shows that using RME is better than expository. Although there is no significant difference on the students’ report, the circumstances of instruction is different. By using RME, students were involved in many activities and they became fun. This supported the students’ report became better than they were teach using expository method.